INSIG-2 promoter polymorphism and obesity related phenotypes: association study in 1428 members of 248 families - Avery Peter J; Rahman Thahira; Hall Darroch H; Keavney Bernard (BMC, 2006)
Abstract Background Obesity is a major public health problem. Body mass index (BMI) is a highly heritable phenotype but robust associations of genetic polymorphisms to BMI or other obesity-related phenotypes have been difficult to establish. Recently a large genetic association study showed evidence for association of the single nucleotide polymorphism (SNP) rs7566605, which lies 10 Kb 5' to the first exon of the insulin-induced gene 2 (INSIG-2), with obesity in several cohorts. We tested this polymorphism for association with body mass related phenotypes in a large family study whose mean BMI was consistent with moderate overweight. Methods We studied 1428 members of 248 British Caucasian families who had been ascertained through a proband with hypertension. We measured BMI, waist and hip circumference, and plasma levels of leptin. We genotyped the rs7566605 SNP using a restriction fragment length polymorphism assay, and carried out a family-based association test for quantitative traits related to obesity using the statistical programs MERLIN and QTDT. Results We observed no significant association between genotype at rs7566605 and covariate-adjusted (for age, sex, alcohol consumption, smoking and exercise habit) log-transformed BMI, waist measurement, hip measurement, waist-to-hip ratio, or plasma levels of leptin. Conclusion There was no association between genotype at rs7566605 and obesity-related phenotypes in this British Caucasian population. These families were in general moderately overweight, few members being severely obese. Our result indicates that this polymorphism has little if any effect on BMI within the normal to moderately overweight range. The effects of this polymorphism on body mass may be restricted to those already predisposed to at least moderate obesity as a result of environmental factors and other predisposing genotypes.